The Use of Remote Sensing and GIS Technology in Supporting Ecoregion Management - Tyas Ismi Trialfhianty; Fajrun Wahidil Muharram; Aldian Giovanno (Jurnal Segara, 2017)
Coastal areas provide great benefits for human lives. In many isolated islands, coastal ecosystem provides food and building materials extracted from coastal vegetation e.g. mangroves. Therefore, it is essential to ensure the sustainability of the coastal ecosystem. This study provides data and a map in supporting the coastal ecoregion management, by using remote sensing satellite imagery, GIS technology, and field observation. Remote sensing and GIS data were obtained from Google Earth and analysed by ArcGIS. The combination of both laboratory and field work were carried out to provide a broad picture of the coastal area in Jefman Island, Raja Ampat, West Papua. The result of this study showed various habitats and vegetation in the Jefman seabed area. It also demonstrates that the abundance and diversity of coral reef and reef fishes are the major community constructing the island, amounting 22% coral cover with 12 families and diversity index 1.20 – 2.52 for reef fish with fish density about 231 ind/50 m2. Furthermore, other communities such as seagrass, seaweed, and mangrove are also briefly explained, as they also play a greater role in supporting the whole coastal ecological system. Based on map data analysis, we found a particular area that urgently needs to be protected. Remote sensing and GIS technology were found useful to help the manager to design coastal management strategies in the future.